An attempt for increasing the efficiency of penning source of Н ⁻ ions with a metal hydride cathode - Sereda, I.; Ryabchikov, D.; Hrechko, Ya.; Babenko, Ie. (Вопросы атомной науки и техники, 2020)
The possibility of increasing the current of negative hydrogen ions extracted in the longitudinal direction from a Penning discharge with a metal hydride cathode by reducing the anode-cathode distance is shown. The features of Н ⁻ ions emission have been revealed depending on the electric shift on the metal hydride cathode and the external magnetic field. The power parameters of the electromagnetic filter have been optimized for the separation of negative ions from the extracted flux of charged particles. The current of H ⁻ ion beam was obtained at the level of 16 μA with hydrogen supply only from the metal hydride cathode and at the level of 0.1 mA at external supply from the balloon. Показана можливість збільшення струму негативних іонів водню, що виходять у поздовжньому напрямку з розряду Пеннінгу з металогідридним катодом шляхом зменшення анод-катодної відстанні. Виявлено особливості емісії іонів Н ⁻ у залежності від електричного зміщення металогідридного катоду і зовнішнього магнітного полю. Оптимізовано параметри живлення електромагнітного фільтра для сепарації негативних іонів з потоку заряджених частинок, що витягується. Отримано струм пучка іонів Н ⁻ на рівні 16 мкА при напуску водню тільки з металогідридного катоду і на рівні 0,1 мА в умовах додаткового зовнішнього напуску з балону. Показана возможность увеличения тока отрицательных ионов водорода, извлекаемых в продольном направлении из разряда Пеннинга с металлогидридным катодом путем уменьшения анод-катодного расстояния. Выявлены особенности эмиссии ионов Н ⁻ в зависимости от электрического смещения металлогидридного катода и внешнего магнитного поля. Оптимизированы параметры питания электромагнитного фильтра для сепарации отрицательных ионов из извлекаемого потока заряженных частиц. Получен ток пучка ионов Н ⁻ на уровне 16 мкА при напуске водорода только из металлогидридного катода и на уровне 0,1 мА в условиях дополнительного внешнего напуска из баллона.